PENGARUH KUALITAS, FITUR DAN MODEL HANDPHONE SONY ERICSSON TERHADAP KEPUASAN KONSUMEN - Setyaningsih Sri Utami, Mima Puji Rahayu & (Universitas Slamet Riyadi, 2012)
ABSTRACT This study examined the effect of quality, features and Sony Ericsson mobile phone models of consumer satisfaction survey on the economics faculty student UniversitasSlamet Riyadi Surakarta. Mobile (cellular telephone) is a communication tool that can connect among fellow men. The presence of mobile phones is a huge leap forward in human history. Cellular technology is the most modern communication technology and the most promising in terms of quality, efficiency and economy. Features found on Sony Ericsson mobile phones include a camera, a browser, wifi, bluetooth, infrared, music player, video player, email, radio, video recording, external memory, Short Message Service, Multi Media Service, and so forth. This study was a survey conducted at the Faculty of Economics, University of Slamet Riyadi are addressed to students regular classroom in Accounting and Management. Samples were performed in non-random sampling is a sampling technique using purposive Accidental Sampling. From the results of the regression model F test used to predict the effect of quality, features, and models of consumer satisfaction is significant. Keywords: Sony Ericsson, quality, features, models contribute, customer satisfaction.